Self-efficacy, perceived training needs and coaching competences: The case of Portuguese handball - Mesquita, I.; Borges, M.; Rosado, A.; Batista, P. M. (European Journal of Sport Science, 2012)
The aim of this study was to analyse handball coaches` perceptions of self-efficacy and recognition of training needs related to coaching competences according to their coaching experience, coach certification level and academic education. Two hundred and seven Portuguese handball coaches answered questionnaires that included a scale of self-efficacy and another of recognition of training needs. Data analysis started with an exploratory factorial analysis with Maximum Likelihood Factoring and Oblimin rotation. From the factors obtained, a One-way ANOVA and Tukey's post hoc multiple comparisons were applied. Coaches` self-efficacy revealed coaching competences related to: annual and multi-annual planning; planning and guiding training and competition; coaching methodology; implementation of sport development projects and coach education and meta-cognitive competences. Coaches` recognition of training needs revealed four main areas: planning and guiding training and competition; multi-annual planning; management of sports careers and coaching education and leadership. Although an independent relationship between coaches` perceptions of self-efficacy and training needs was confirmed, they perceived themselves as having competences and highlighted training needs in all areas. Coaches` perceptions of self-efficacy were influenced by their coach certification level, academic education and coaching experience. The study suggests that sport specificity within the social culture in addition to the precise sporting domain of action influence the perceptions of coaches about their self-efficacy and training needs as related to coaching competences and, therefore, should be considered in the coach education curriculum.